Solution of two-dimensional parabolic equation with nonlocal integral boundary conditions - Jakubelienė, Kristina (Lietuvos matematikos rinkinys, 2011)
Two-dimensional parabolic equation with nonlocal integral boundary conditions in a rectangle domain in this paper is solved by  alternating direction method. To ﬁnd the solutions of this problem we are looking to solve a linear system of equations. This algorithm is realized on particular example and assess the error of solution.
Keywords: two-dimensional parabolic equation; nonlocal integral condition; ﬁnite-diﬀerence method; alternating direction method